Coordinated histone modifications are associated with gene expression variation within and between species - Ha, M.; Danny W-K. Ng; Li, W.; Chen, Z.J.
Histone modifications regulate gene expression in eukaryotes, but their effects on transcriptomes of a multicellular organism and on transcriptomic divergence between species are poorly understood. Here we present the first nucleotideresolution maps of histone acetylation, methylation, and core histone in Arabidopsis thaliana and a comprehensive analysis of these and all other available maps with gene expression data in A. thaliana, Arabidopsis arenosa, and allotetraploids. H3K9 acetylation (H3K9ac)and H3K4 trimethylation (H3K4me3)are correlated, and their distribution patterns are associated with Gene Ontology (GO)functional classifications. Highly dense and narrow distributions of these modifications near transcriptional start sites are associated with constitutive expression of genes involved in translation, whereas broad distributions toward coding regions correlate with expression variation of the genes involved in photosynthesis, carbohydrate metabolism, and defense responses. Compared to animal stem cells, dispersed distributions of H3K27me3 without bivalent H3K4me3 and H3K9ac marks correlate with developmentally repressed genes in Arabidopsis. Finally, genes affected by A. thaliana histone deacetylase 1 mutation tend to show high levels of expression variation within and between species. The data suggest that genome-wide coordinated modifications of histone acetylation and methylation provide a general mechanism for gene expression changes within and between species and in allopolyploids.